CAN BASAL CUTTING BLADE WEAR AFFECT SUGARCANE REGROWTH? - Bernache, Leonardo [UNESP]; Tedesco-Oliveira, Danilo [UNESP]; Oliveira, Luan P. de [UNESP]; Correa, Ligia N. [UNESP]; Silva, Rouverson P. da [UNESP] (Soc Brasil Engenharia Agricola, 2020)
Sugarcane harvester cutting blade wear increases ratoon damages and losses, impairing sugarcane regrowth. This study aimed to evaluate the quality of basal cut using ratoon damage and loss indexes and correlating them with effects on sugarcane regrowth. Harvest parameters such as plant height and position, damage and loss indexes, and stem length were evaluated every 30 min, following statistical process control (SPC) assumptions. Blade wear was examined during three harvesting shifts (0-8 h, 8-16 h, and 16-24 h). Sugarcane regrowth was assessed by counting number of tillers and measuring plant height and stem diameter. The second harvesting shift showed better quality in terms of damage and loss indexes, and plant height and stem diameter. Harvesting was considered out of control for parameters such as cutting height, number of tillers, plant height, and stem diameter. On the other side, it was regarded as under control for damage and loss indexes, and plant high and position. The first shift presented peripheral or no damages and weak to medium loss levels, whereas the second and third ones showed extreme damages and medium to strong losses.
Keywords: Mechanized; harvesting; Sugarcane; SPC; Harvester